Technology Acceptance in Higher Education: Google Apps through the Lens of the Theory of Planned Behavior - Noori Dagman , Sarah; Radif, Mustafa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2024)
This paper examines the acceptance of Google Apps in higher education through the lens of the Theory of Planned Behavior (TPB). It explores the relationship between attitudes, subjective norms, perceived behavioral control, and the intention to use Google Apps among university professors. The study reviews previous research on the factors influencing the adoption of Google Apps and TPB’s application in educational settings. The findings provide insights into enhancing the integration of digital tools in educational environments.